2003
DOI: 10.1046/j.1523-1739.2003.01418.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Prairie Fragmentation on the Nest Success of Breeding Birds in the Midcontinental United States

Abstract: Grassland fragmentation and habitat loss are hypothesized to be contributing to widespread grassland bird declines in North America due to the adverse effects of fragmentation on breeding bird abundance and reproductive success. To assess the effects of fragmentation on the reproductive success of grassland birds, we measured rates of nest predation and brood parasitism for four species of birds ( Grasshopper Sparrow [Ammodramus savannaru], Henslow's Sparrow[Ammodramus henslowii], Eastern Meadowlark [ Sturnell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
114
2
5

Year Published

2004
2004
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 185 publications
(127 citation statements)
references
References 23 publications
6
114
2
5
Order By: Relevance
“…This work suggested that for smaller grassland songbirds, the large core area of the BCA was not necessary, as reproductive success on the smaller grassland patches was not consistently different from that on larger patches (Winter et al 2006). This is not surprising, as other studies of grassland birds had suggested that these species responded positively to small tracts of habitat, requiring smaller areas of acceptable habitat within their landscape than forest birds might (McCoy et al 1999, Herkert et al 2003. Unfortunately, the validity of the BCA concept for species as large as prairie-chickens or Northern Harrier (Circus cyaneus) has not been tested; we not only lack a good idea of how large a landscape is needed to support smaller migratory grassland birds, but we also do not know if the BCA concept would work to save prairie grouse populations, many of which are declining.…”
Section: Is Our Science Sufficient To Guide Conservation Efforts For mentioning
confidence: 86%
“…This work suggested that for smaller grassland songbirds, the large core area of the BCA was not necessary, as reproductive success on the smaller grassland patches was not consistently different from that on larger patches (Winter et al 2006). This is not surprising, as other studies of grassland birds had suggested that these species responded positively to small tracts of habitat, requiring smaller areas of acceptable habitat within their landscape than forest birds might (McCoy et al 1999, Herkert et al 2003. Unfortunately, the validity of the BCA concept for species as large as prairie-chickens or Northern Harrier (Circus cyaneus) has not been tested; we not only lack a good idea of how large a landscape is needed to support smaller migratory grassland birds, but we also do not know if the BCA concept would work to save prairie grouse populations, many of which are declining.…”
Section: Is Our Science Sufficient To Guide Conservation Efforts For mentioning
confidence: 86%
“…Rates of nest predation on grassland birds, including the Bobolink, decline only on large habitat fragments (≥ 1,000 ha; Herkert et al, 2003). Nest predation rates are generally higher near forest edges and decline as the distance from forest edges increases (Johnson and Temple, 1990;Bollinger and Gavin, 2004;Renfrew et al, 2005).…”
Section: Habitat Fragmentation and Nest Predationmentioning
confidence: 99%
“…Habitat composition and configuration at scales greater than an individual breeding territory have been predictive of nest success for some grassland species (Greenwood et al 1995, Herkert et al 2003, Skagen et al 2005, but see Winter et al 2005). We defined an area~3 times the size of a large territory as a neighborhood.…”
Section: Neighborhood-scale Habitat Metricsmentioning
confidence: 99%